Hereditary hypotrichosis simplex of the scalp - Hamideh Moravvej-Farshi; Azin Ayatollahi; Somayeh Hejazi (Wolters Kluwer Medknow Publications, 2014)
Hereditary hypotrichosis simplex of the scalp is a genetic disorder, characterized by sparse or absent scalp hair without structural defects, in the absence of other ectodermal or systemic abnormalities. Structural hair defects may be presented with a genetic disorder affecting hair growth or part of a congenital syndrome or may indicate underlying metabolic disorders, or may be associated with other diseases. We describe a 26-years-old Persian girl suffering from hypotrichosis simplex of the scalp with trichorrhexis nodosa who had no ectodermal defects and systemic disease.